The incidence of polyneuropthy and its relation with disease parameters in chronic obstructive pulmonary disease - Ogan, Nalan; Sayın, Refah; Baha, Ayşe; Akpınar, Evrim Eylem; Gülhan, Meral (The European Research Journal, 2019)
Objective: Chronic Obstructive Pulmonary Disease (COPD) is accompanied by several concomitant conditions due to its systemic effects. Hypoxia and oxidative stress associated with COPD are also believed to contribute to the disease course through the effects of several inflammatory mediators. Major causative agents causing of peripheral neuropathy are age, hypoxia, duration and severity of COPD, hypercapnia and smoking. The present study aimed to investigate the incidence of polyneuropathy and its relation with disease parameters in COPD patients. Methods: Of a total number of 45 patients who had been followed up between January 1, 2015 and December 31, 2016 with a diagnosis of COPD at Ufuk University School of Medicine were enrolled retrospectively. All patients underwent electroneuromyography, arterial blood gas measurements and pulmonary function tests. Patients were divided as those with or without neuropathy, and factors contributing to the development of neuropathy were investigated based on clinical and laboratory findings. Results: Eleven (24.4%) patients were women and 34 (74.6%) were men, and the mean age was 73.2 years. Mean PaO2 was 58.2 mmHg, pCO2 was 41.2 mmHg, and FEV1 was 45.3%. Neuropathy was diagnosed in twenty (44.4%) patients. Significant differences were found in pO2, pCO2, SO2, mMRC, smoking status and number of exacerbations per year (p < 0.05). Conclusions: Patients who experience frequent exacerbations and those with hypoxemia or hypercapnia as demonstrated should be taken into more careful clinical assessments with respect to polyneuropathy.